(untitled) (Perner’s Contacts, 2011)
This contribution describes a determination of maximum height of the cap of crosssectional area of the belt conveyor with one-idler set on the basis of known value of useable conveyor belt width. At the same time is determined the biggest crosssectional area of belt conveyor with three-idler set assuming that the values of surcharge angle, conveyor belt width, troughing angle and length dimensions of idlers are known as well.